Pengaruh Karakteristik Penumpang Pesawat Terhadap Peluang Pemilihan Moda Menuju Bandara Baru Kulonprogo - Wibowo, Wahadi; Rudiarto, Iwan (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The growth of air passengersÂ impacted not only on the addition of fleets number and flight routes, but also on the provision of airports and facilities. Airport facilities are not only about terminal space and air-side facilities, but also related to the provision of intermodal facilities to and from the airport. In Indonesia, some airports have increased number of passengers, and some of them decided to move the old airport to a new location. Adi Sutjipto Airport in Yogyakarta plans to move its location to Kulonprogo district which is still in Yogyakarta province. The existence of a new location in Kulonprogo will affect on the selection of transportation modes. On the other hand, the mode choice goes to the new airport are not just overcome, but there are some characteristics factor from the passengers which are influence it . The passengers characteristics are the distance, kind ofÂ jobs, the monthly income, private vehicle ownership, the age level and the genders of passengers.Â The analytical techniques in this study are quantitative descriptive with clustering based on certain criteria using cross tabulation techniques. This study was carried out by giving a questionnaire on air passengers in Adi Sutjipto airport to gain an understanding of their characteristics and their selection of modes transport used when the new airport will be operate. The result of the research is the existence of relationship between characteristics of air passengers with the selection of modes transport to the new airport. Preference for the modes selection to new airport can be taken into consideration in decision-making related to the development of inter-mode facilities to the new airport in Kulonprogo in the future.